Perancangan Koleksi Pakaian Wanita yang Memberikan Ruang Gerak dan Kenyamanan Untuk Brand Catherine Yuwono - Yuwono, Catherine; Tanzil, Marini (Jurnal VICIDI, 2020)
Catherine Yuwono brand collection is created to provide comfortable and flexible clothing for career women who have high mobility in their daily life. Target market of brand Catherine Yuwono is young career women who are the combination of consumer type Actualizers and Fulfilleds. After passing through the research process by interviewing the experts and potential costumers, observation, and literature studies, the collection of 5 ready to wear garments were made. This women’s wear collection design hopefully could be well received and answer the identified problems.